2017
DOI: 10.1016/j.jaut.2016.09.009
|View full text |Cite
|
Sign up to set email alerts
|

In vivo effector functions of high-affinity mouse IgG receptor FcγRI in disease and therapy models

Abstract: Two activating mouse IgG receptors (FcγRs) have the ability to bind monomeric IgG, the high-affinity mouse FcγRI and FcγRIV. Despite high circulating levels of IgG, reports using FcγRI or FcγRIV mice or FcγRIV-blocking antibodies implicate these receptors in IgG-induced disease severity or therapeutic Ab efficacy. From these studies, however, one cannot conclude on the effector capabilities of a given receptor, because different activating FcγRs possess redundant properties in vivo, and cooperation between Fcγ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 41 publications
(90 reference statements)
1
9
0
Order By: Relevance
“…Since the IgG concentration in alveoli is much lower than in plasma, we hypothesize that FcγRI is partially unoccupied, making it a true high-affinity receptor for IgG-opsonized microbial agents. This is in line with recent publications that show that FcγRI is not fully saturated by IgG, neither in mice [32] nor in humans [33], making it readily available for immune complexes.…”
Section: Discussionsupporting
confidence: 91%
“…Since the IgG concentration in alveoli is much lower than in plasma, we hypothesize that FcγRI is partially unoccupied, making it a true high-affinity receptor for IgG-opsonized microbial agents. This is in line with recent publications that show that FcγRI is not fully saturated by IgG, neither in mice [32] nor in humans [33], making it readily available for immune complexes.…”
Section: Discussionsupporting
confidence: 91%
“…This suggested that the binding of the anti- NK1.1 and anti-NKp46 mAbs was not mediated by FcγRIIB on B cells. This conclusion was corroborated with the use of FcγRIIB-deficient mice and FcγR-deficient mice lacking FcγRI, FcγRIIB, FcγRIII, and FcγRIV (Gillis et al, 2017). The frequencies of CD19 + cells that co-stained with anti-NK1.1 (CD19 + NK1.1 + C57BL/6 mice: 0.045 ± 0.002; FcγRIIB-deficient mice: 0.06 ± 0.003; FcγR-deficient mice: 0.06 ± 0.002; mean ± SEM) or anti-NKp46 (data not shown) were similar between the mutant strains and the wild-type strain.…”
mentioning
confidence: 71%
“…Inflammation triggered by autoantibodies depends on several processes, which are initiated by the formation of antibody-antigen ICs (41). In the K/BxN serum transfer model, IgG IC-mediated cross-linking of activating FcγRs on neutrophils is essential for the development of joint inflammation (8,10,42), which in turn can be suppressed by the inhibitory FcγR2b (43,44). Mouse neutrophils have a clear basal expression of activating FcγR3 (CD16) and FcγR4 (CD16-2) (SI Appendix, Fig.…”
Section: Csf3 Is An Inflammation-related Neutrophil Il-4rα-regulatingmentioning
confidence: 99%